The Usage of Online Database by Graduate Students at RajabhatMahasarakham University - Apamo, Woraphat; Sudsuansi, Yanin (Journal of Graduate MCU KhonKaen Campus, 2019)
The purposes of this research were to study the use online database bygraduate students at RajabhatMahaSarakham University, to study problems from using online database in office an academic resourcesand information technology at RajabhatMahaSarakham University. The research employed the survey methodology. The research used a questionnaire for collecting data. The samples were 217 graduate students who studied a Master’s degree and a Doctorate at RajabhatMahaSarakham University. Data analyzed by using percentage, mean, and standard deviation. The research findings were as follows: 1. Online database usage of graduate students 1.1 Graduate students accessed online database not over 3 times a month. Source of information about online database was the website of office an academic resourcesand information technology. They learned the process to access online database from the suggestion of the librarians and accessed online database from their houses. 1.2 Graduate students used online database for making research and theses. They save the files and read them from their laptops. Users agreed that an advantage of online database was to able for searching information 24 hours. In addition, ScienceDirect was the online database which used the most from total online database in office an academic resourcesand information technology. 2. The problems of online database usage were totally at a medium level which arranged from the highest to the lowest as service person,library userand network and computer, respectively. If arranged in area and item i.e. service person area- the public relations about using online database was not widespread, library user area- graduate students could not manage the result from searching online database, and network and computer area- the network was not stable and weak.